The interdisciplinary approach to the management of chronic knee pain in the elite athlete - a case study - Wallace, A.; Biswas, A.; Rosenblatt, B. (The Sport and Exercise Scientist, 2012)
The athlete completed a comprehensive week at the IRU and was discharged back to the care of his own support team with suggestions for both clinical and training strategies to continue to progress his rehabilitation. He made a full recovery. This case study highlights how long-term injury at a local site can be caused by long-term strains in other parts of the body (Myers 2009). An injury may manifest locally because of a remote inherent weakness, or a seemingly unrelated previous injury, and not solely due to local strain. Identifying these pathways with an integrated, clinically-led and scientifically-based strategy allows effective release of chronic strain and restoration of systemic function.